PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN NASABAH PT BANK CENTRAL ASIA, TBK CAB KYAI CARINGIN: PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN NASABAH PT BANK CENTRAL ASIA, TBK CAB KYAI CARINGIN - Joni Tesmanto,; Surry Putri Rustiani (Jurnal Publikasi Manajemen Informatika, 2022)
PT Bank Central Asia, Tbk KCP Kyai Caringin continues to raise public funds. To achieve this, we need the right strategy through optimal service by improving product quality and offering it to customers according to customers desires and needs, as well as providing the best service. Effort to provide optimal service to customers must pay attention to the factor needed by customers. Customer satisfaction is very important because by knowing the level of customer satisfaction, we can find out how far the quality of services provided by employees has an effect on customer satisfaction